Research progress on transcranial direct current stimulation for improving muscle strength: a narrative review - Zhang, Yiguang; Zhang, Yi; Song, Yu; Wu, Huaduo; Gao, Xin; Dong, Yumo; Jiang, Ning (Frontiers in Neurology, 2026)
Muscle strength plays a fundamental role in enhancing sports performance, preventing sports injuries, and improving overall quality of life. In recent years, transcranial direct current stimulation (tDCS) has garnered significant attention in the field of motor performance enhancement. As a non-invasive brain stimulation technique, tDCS applies weak, constant direct current through electrode plates placed on the scalp to modulate neural excitability in specific areas of the cerebral cortex. However, the effects of tDCS on improving muscle strength remain inconsistent, and its exact mechanisms are still unclear. Further research is warranted to clarify its efficacy. This review summarizes research on the influence of tDCS interventions on muscle strength, focusing on maximum muscle strength, explosive power, and muscle endurance. It aims to analyze the outcomes of tDCS interventions across various sports tasks, and to discuss potential mechanisms through which tDCS may affect muscle strength. The collected evidence suggests that tDCS has the potential to influence muscle strength; however, considerable variations in its effects on athletes’ specific skills may be related to individual differences and varying stimulation protocols. This review consolidates existing evidence and offers relevant suggestions for future research, providing a theoretical foundation for the application of tDCS to improving muscle strength.